Southern Africa and Agro-processing: Investigating the state of agricultural RVCs and the role of South African food retailers in regional supplier development - Gorven, Ruth (School of Economics, 2022)
Regional integration in southern Africa must enable wide-spread economic benefits. Agroprocessing value chains could play a significant role in pursuing this kind of growth but can only do so with public-private collaboration and strong developmental regionalism. Agricultural and agro-processing regional value chains are a mechanism through which countries can upgrade their production capabilities, while supporting poor communities and driving economic development. Unfortunately, current growth and trade performance indicates that these sectors have not reached their potential. Variability and volatility in agriculture, practical challenges of trade facilitation, and slow growth in agro- processing have limited the industry's impact on development. South Africa's trade dominance also leads to political resistance to further regional integration. These challenges limit other southern African countries from upgrading in this industry by restricting development of regional value chains, preventing agro-processing industries from achieving global competitiveness. Case studies of supermarkets' engagement in the region and Nando's supplier development programmes provide a qualitative assessment of why agro-processing has not expanded significantly, and what steps might be taken to stimulate its growth. The role of supermarkets in regional agro-processing is significant, but their contribution toward the industry's development has so far had limited impact. Case studies show supermarkets do operate some effective supplier development programmes but face severe challenges. The Nando's Peri Farms Initiative provides an example of an effective supplier development programme, balancing business with socially oriented outcomes. The programme invests in regional suppliers and guarantees prices to small scale farmers. This ensures that farmers in the project experience improvements in their standards of living and business prospects, while also securing Nando's business interests. This kind of programme may be scalable to other firms, but requires incentives from government, aid donors, or NGOs to encourage large firms to pursue socially beneficial objectives. Further research into the role of firms like Nando's and the scalability of Peri Farms Initiativestyle projects is needed in order to understand how the expansion of supplier development could pursue developmental outcomes and the growth of equitable regional value chain participation. Additional investigation into the role of incentives for private firms through government or nongovernmental organisation (NGO) involvement would be valuable. Furthermore, this kind of programme may be applicable to food suppliers and producers, and research of those industries could broaden the impact of this research.